Perhitungan Laba Serta Titik Impas Melalui Analisis Cost Volume Profit (CVP) (Studi Kasus UMKM Dakak-Dakak Dapur Mas) - Mega Rahmi; Ramadanis Ramadanis; Diva Fadillah Ramika; Jenny Selvia; Nanda Hasfizanurizal; Nania Desriana (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the relationship between costs, sales levels, and profits at Dakak-dakak Dapur Mas MSMEs by applying product mix-based Cost volume profit (CVP) analysis. The research method used is quantitative descriptive with primary data sources collected through observation and interviews. The analysis focused on calculating fixed and variable costs, contribution margin, Break Even Point (BEP), Margin of Safety (MoS), and Operating Leverage. The results showed that under normal sales conditions, the MSME was able to generate a profit of IDR 14,786,241, with the largest profit contribution coming from the Benai product. However, the BEP analysis found a loss of IDR 53,596 due to one of the products, Bungo Durian, not reaching the break-even point. The safe limit for sales decline is indicated by an MoS value of 98 kg for Karambia Cake, 420 kg for Bungo Durian, and 434 kg for Benai. The Operating Leverage value of 1.72 indicates that changes in sales volume have a significant impact on profit. If profit increases by 10%, the total profit of MSMEs is estimated to reach IDR 17,344,113. These findings confirm that CVP analysis can be used as an effective basis for profit planning and production decision-making in MSMEs with a variety of products.